2020
DOI: 10.3390/healthcare8020151
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country Differences and Similarities in Undernutrition Prevalence and Risk as Measured by SCREEN II in Community-Dwelling Older Adults

Abstract: Undernutrition is highly prevalent among community-dwelling older adults. Early identification of nutrition risk is important to prevent or treat undernutrition. This study describes the prevalence rates of nutrition risk in community-dwelling older adults (aged ≥ 65) using the same validated tool across different countries and aims to identify differences in nutritional risk factors. Cross-sectional data was obtained from three datasets including participants from the Netherlands (NL), Canada (CA) and New Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…Our study showed that nearly 75% of people over 60 years of age were at high nutritional risk. Similarly, studies carried out in Canada, New Zealand, and the Netherlands have reported high proportions of elderly people at high nutritional risk (61.5–70.1%) [ 23 ]. Elements that may have influenced the difference in the proportion of people found in our study to be at high nutritional risk include the final number of participants (320 vs. 13,340); it should be taken into account that our study included only two provinces in Poland, whereas the study by Borkent et al (2020) [ 23 ] examined three countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that nearly 75% of people over 60 years of age were at high nutritional risk. Similarly, studies carried out in Canada, New Zealand, and the Netherlands have reported high proportions of elderly people at high nutritional risk (61.5–70.1%) [ 23 ]. Elements that may have influenced the difference in the proportion of people found in our study to be at high nutritional risk include the final number of participants (320 vs. 13,340); it should be taken into account that our study included only two provinces in Poland, whereas the study by Borkent et al (2020) [ 23 ] examined three countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies carried out in Canada, New Zealand, and the Netherlands have reported high proportions of elderly people at high nutritional risk (61.5–70.1%) [ 23 ]. Elements that may have influenced the difference in the proportion of people found in our study to be at high nutritional risk include the final number of participants (320 vs. 13,340); it should be taken into account that our study included only two provinces in Poland, whereas the study by Borkent et al (2020) [ 23 ] examined three countries. In addition, the majority of respondents in our study were 60–74-year olds (73.6%) ( Table 2 ), while in the aforementioned study, 65.8% were 65–74-year olds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately two-thirds of older adults in Canada are identified as having nutrition risk [ 4 ]. It is recognized that better screening as well as identifying opportunities for prevention could help older adults retain their independence and improve their quality of life as well reduce hospital length of stay and associated costs.…”
Section: Discussionmentioning
confidence: 99%
“…Using standardized methodology and cut-points, a tri-country study (Canada, New Zealand, The Netherlands) found a uniformly high prevalence of high nutrition risk (61.5–70.1%) in community-dwelling adults ≥65 years of age [ 4 ]. The validated screening tool (SCREEN II) is considered useful for identifying upstream factors (e.g., determinants of food intake such as grocery shopping difficulty) that may predict future as well as current malnutrition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%